The Advent of the COVID-19 Epidemic Did Not Affect Americans’ Endorsement of Moral Foundations - Vartanova, Irina; Eriksson, Kimmo; Kirgil, Zeynep Melis; Strimling, Pontus (Frontiers in Psychology, 2021)
Prior work has suggested that existential threats in the form of terror attacks may shift liberals’ reliance on moral foundations to more resemble those of conservatives. We therefore hypothesized that endorsement of these moral foundations would have increased when the COVID-19 epidemic became a salient threat. To examine this hypothesis we conducted a longitudinal study with 237 American participants across the liberal-conservative spectrum, in which their endorsement of various moral foundations were measured before and after the advent of the pandemic. We did not find evidence of any systematic change in the endorsement of any moral foundation, neither in general nor specifically among liberals or specifically among those who perceived the greatest threat from COVID-19. We conclude that the threat from the pandemic does not seem to have had any substantial effect on the moral foundations that people rely on. We discuss how this finding relates to other longitudinal studies of the effect of the COVID-19 pandemic on measures related to conservatism.